2017
DOI: 10.1515/npf-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Do Government and Foreign Funding Influence Individual Donations to Religious Nonprofits? A Survey Experiment in Pakistan

Abstract: Donors support faith-based organizations whose missions and work cohere with their religious values. Might such donors located in the local community be less likely to donate to a hypothetical Madrasa, an Islamic seminary providing K-12 education, which receives funding from non-local sources, specifically the federal government or foreign donors? We examine this question using a survey experiment in Lahore, Pakistan. Because some Madrasa students have indulged in acts of terrorism, the government of Pakistan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Nevertheless, we cannot discard the possibility of anti-Western sentiments about NGOs that are likely to affect their work. For instance, some recent research showed that foreign financial support and anti-Western sentiments can influence the perception and support to local NGOs in Pakistan (Wasif, 2020; Wasif & Prakash, 2017), with variations across subsamples (e.g., elites vs. general population). Interestingly, islamophobia seems to also influence support for Islamic charities (Tremblay-Boire & Prakash, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, we cannot discard the possibility of anti-Western sentiments about NGOs that are likely to affect their work. For instance, some recent research showed that foreign financial support and anti-Western sentiments can influence the perception and support to local NGOs in Pakistan (Wasif, 2020; Wasif & Prakash, 2017), with variations across subsamples (e.g., elites vs. general population). Interestingly, islamophobia seems to also influence support for Islamic charities (Tremblay-Boire & Prakash, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Turkey has cracked down on Kurdish nonprofit groups. Similarly, despite operating in a Muslim-majority country, many Muslim religious charities in Pakistan believe the government discriminates against them because of their explicit Muslim identity (Wasif & Prakash, 2017). While there is research focusing on the Global South, there remains a gap in the literature on government distrust among nonprofits operating in the Global North.…”
Section: Literature Reviewmentioning
confidence: 99%